Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis